2021
DOI: 10.1111/jocn.15996
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ experiences with simulation‐based education as a pedagogic method in low‐resource settings: A mixed‐method study

Abstract: Aims and Objectives:This study introduced simulation-based education in nurse education programs in Tanzania and Madagascar and explored nursing students' experiences with this pedagogic method as a mode of learning.Background: Simulation-based education has barely been introduced to education programs in resource-constrained settings. The study was conducted in two nurse education programs: one in rural Tanzania and the other in the mid-land of Madagascar.Both institutions offer diploma programs in nursing. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In recent years, research shows that the application of virtual simulation technology and methods in nursing teaching can achieve good teaching results. Nursing students are satisfied with simulation as a teaching method [38], and think that simulation improves their ability and prepares for professional practice [39]. Green G et al evaluated the impact of basic nursing practice on nursing students' ability and learning satisfaction at three time points: before simulation (T1), after simulation (T2) and one month after simulation (T3).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research shows that the application of virtual simulation technology and methods in nursing teaching can achieve good teaching results. Nursing students are satisfied with simulation as a teaching method [38], and think that simulation improves their ability and prepares for professional practice [39]. Green G et al evaluated the impact of basic nursing practice on nursing students' ability and learning satisfaction at three time points: before simulation (T1), after simulation (T2) and one month after simulation (T3).…”
Section: Discussionmentioning
confidence: 99%
“…Students and members of the healthcare workforce who have had the opportunity to use simulation in their training place a high value on this novel teaching method. Bo et al . (2022) discovered that simulation helped students develop confidence, improve clinical competencies and master theoretical content in their studies conducted in Tanzania and Madagascar.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in their Tanzania and Madagascar study, Bø et al (2022) reported that simulation helped train nurses who were competent and well equipped to enter the clinical setting. They also stated that role-playing scenarios improved nursing students' mastery of the theoretical content.…”
Section: Improved Confidence and Competencementioning
confidence: 99%
See 1 more Smart Citation
“…Nursing simulation has been used to improve the quality of patient care in assorted real‐life scenarios in primary care, such as hypoglycaemia‐coma and anaphylaxis‐cardiac arrest or suicidal attempts, by providing nursing students and health care professionals with clinical skills, critical and problem‐solving thinking (Dryver et al, 2021). A number of studies have attempted to understand nursing students' experiences and perceptions with simulation as a learning method, outlining confidence, independence and active participation as deciding attributes that make simulation a truthful representation of the clinical reality to which students will be exposed in the long term (Bø et al, 2021; Mulli et al, 2022; Saaranen et al, 2020). By using this educational resource to simulate health situations that are closely related to environmental factors, such as acute pesticide poisonings, it is possible to immerse the student in a complex context where a multi‐elemental perspective will be required to develop the necessary action and prevention strategies (Basak et al, 2016; Jin & Choi, 2018).…”
Section: Introductionmentioning
confidence: 99%